Gender and citizenship: textbooks’ limits and possibilities for history teaching: Gender and citizenship: textbooks’ limits and possibilities for history teaching (Revista de História da UEG (REVHIST), 2020)
Textbooks are complex and multifaceted cultural objects for it materializes the marketing, ideological and pedagogical aspects of its own production. Considered essential instruments for the history teaching, which has a fundamental role in forming citizens, the textbooks maintain a thorough relation with the historical knowledge and therefore with the edification of citizenship. Wherefore, the goal of this article is to analyze, from the feminist theory and the gender studies, the limits and the possibilities of the Projeto Radix – Raiz do Conhecimento (2013) textbook, and to discuss the citizenship concept, specifically in the narrative about the Brazilian women’s and feminists’ social movements in the process of Brazil’s democratization and the elaboration of the country’s Constitution in 1988.Keywords: Textbook. Feminism. Citizenship. History teaching.